Review Mengenai Peningkatan Kuat Tekan Beton Dengan Natural Fiber Reinforced Polymer (NFRP) - Ramadanas, Rian Fajri; Idriansyah, Yomi; Mufarizal, Muhammad (Dept. of Civil Engineering Universitas Riau, 2024)
Damaged buildings require structural reinforcement. This journal uses external restraints with Natural Fiber Reinforced Polymer (NFRP) material because Fiber Reinforced Polymer (FRP) material requires relatively expensive costs and a production process that is not environmentally friendly. This research review aims to determine the behavior of confined concrete with external Natural Fiber Reinforced Polymer (NFRP) and the increase in compressive strength due to confinement. The test is carried out by providing an axial load on the concrete test object which is restrained by NFRP. NFRP restrained specimens are made by wrapping the entire concrete in a circle using natural fibers and adhesives. The results obtained from this research review are the compressive strength of confined concrete using several types of natural fibers such as jute, hemp, cotton, abaca and basalt, it is found that the type of fiber and the number of layers of NFRP affect its compressive strength. NFRP showed a significant restraining effect on increasing the compressive strength and increasing the ductility of the concrete. The increase in strength and ductility will increase with an increase in the number of layers of Natural Fiber Reinforced Polymer (NFRP).